2001
DOI: 10.1001/archneur.58.6.961
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Multiple Sclerosis Functional Composite as an Outcome Measure in a Phase 3 Clinical Trial

Abstract: The MSFC demonstrated excellent intrarater reliability in this multinational phase 3 trial. Three prebaseline testing sessions were sufficient to compensate for practice effects. The pattern of correlations among the MSFC, its components, and the Kurtzke Expanded Disability Status Scale supported the validity of the MSFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
1
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 21 publications
6
135
1
6
Order By: Relevance
“…42 The primary outcome measure was change in the MS Functional Composite score (MSFC), an outcome measure that combines three domains: upper arm and hand function, cognition, and ambulation; it is expressed as a composite Z-score. 43 Two-year worsening in MSFC was reduced by 40.4% (P ϭ 0.033) in the treatment arm; this was attributable largely to preservation of upper extremity function as measured by the nine-hole peg test. There was a significant reduction in relapses, but no difference between groups in the progression of EDSS.…”
Section: Secondary Progressive Msmentioning
confidence: 87%
“…42 The primary outcome measure was change in the MS Functional Composite score (MSFC), an outcome measure that combines three domains: upper arm and hand function, cognition, and ambulation; it is expressed as a composite Z-score. 43 Two-year worsening in MSFC was reduced by 40.4% (P ϭ 0.033) in the treatment arm; this was attributable largely to preservation of upper extremity function as measured by the nine-hole peg test. There was a significant reduction in relapses, but no difference between groups in the progression of EDSS.…”
Section: Secondary Progressive Msmentioning
confidence: 87%
“…However, the individuals with MS achieved a significantly lower maximal heart rate (beats per minute) than the controls during the exercise test (p = 0.02), with a Cohen d effect size of 1.36 (which is considered large [10]). Despite not reaching statistical significance between groups, VO 2 peak and peak workload had large effect sizes (0.98 and 0.97, respectively) ( The mean between-leg Table 1.…”
Section: Whole Body Oxygen Uptakementioning
confidence: 93%
“…23 Before randomization, the 436 patients underwent three pre-baseline MSFC testing sessions. The MSFC had excellent intra-rater reliability, with an intraclass correlation coefficient of 0.90 for session three (final pre-baseline session) and session four (baseline session).…”
Section: Reliabilitymentioning
confidence: 99%
“…Several studies have demonstrated a moderately strong correlation between the MSFC and EDSS. 17,23,25 MRI measures, such as T1 and T2 lesion load, also correlate significantly with MSFC scores. 26 Additionally, one study found a moderately strong correlation between the MSFC and measures of brain atrophy in patients with relapsing-remitting MS Multiple Sclerosis Predictive criterion validity is the ability of an instrument to predict future disease status.…”
mentioning
confidence: 91%
See 1 more Smart Citation